Biotransformations with Photobiocatalysts for Enantioselective Ester Hydrolysis - Agnieszka Śliżewska; Paulina Majewska; Ewa Żymańczyk-Duda (Molecules)
This study investigates the efficient and enantioselective hydrolysis of ester bonds through a series of biotransformations employing various photobiocatalysts. A racemic mixture of 1-phenylethyl acetate served as the model substrate. The described research identified three strains exhibiting the highest biocatalytic activity: Nostoc cf-muscorum (CCALA 129), Leptolyngbya foveolarum (CCALA 76), and Synechococcus bigranulatus (CCALA 187). Their application led to the complete hydrolysis of the starting reagent, yielding both the unreacted ester and its corresponding alcohol in an enantioselective manner. Notably, the selectivity, expressed as S, reached an impressive value of 283 in certain outcomes. The photobiotransformations were conducted under varying conditions, with particular focus on two essential parameters: the duration of the process, crucial for kinetically controlled reactions, and light exposure, critical for light-dependent organisms. The representative results highlight the efficacy of these biocatalysts. For instance, using Leptolyngbya foveolarum (CCALA 76), Nostoc cf-muscorum (CCALA 129), and Synechococcus bigranulatus (CCALA 187) facilitated the production of 1-(R)-phenylethanol with enantiomeric excesses (ee) of 89%, 88%, and 86%, respectively, at a conversion degree of approximately 50%. These processes also yielded an optically enriched mixture of the unreacted substrate, 1-(S)-phenylethyl acetate. Specifically, in the case of Leptolyngbya foveolarum (CCALA 76), the ee of the unreacted ester reached up to 98%. Light exposure emerged as a key factor influencing selectivity factor (S). Adjusting this parameter allowed us to achieve an E value of up to 283 for the formation of 1-(R)-phenylethanol with an ee > 99% when utilizing the Nostoc cf-muscorum (CCALA 129) strain. Furthermore, light intensity proved crucial for scaling up these processes. Significant results were obtained with Synechococcus bigranulatus, particularly at substrate concentrations ranging from 1 to 10 mM under limited exposure. Here, the conversion degree was 55%, the ee of the (R)-alcohol was 86%, and the selectivity factor (S) value was 21.